La teoría de las uniones aduaneras y el Pacto Andino - Simons Chirinos, Andrés (1992)
This paper examines the Peruvian alternatives before the Andean Group integration scheme. The importance of this analysis is related to the decision of permanence that the Peruvian government shall take at the end of 1993. The start point is the pure theory of customs unions, its principal topics and ways of thinking. The essay establishes generical conditions under which an integration process results beneficial. The evaluation reverts also to an analysis of the last agreements and decisions taken under the frame of the Andean Group.